Specialist artisans and commodity producers as social actors in early medieval Britain, c. AD 500-1066 - Loveluck, Chistopher (Ecole francaise de Rome, 2016)
This contribution explores the many questions that need to be asked in regard to how specialist craft-working was organised in early medieval Britain, and how specialist artisans and traders exercised initiative as social actors. A particular emphasis is placed on exploring their activities within the context of their family dynamics and changing social and settlement hierarchies, between c. AD 500 and 1066. The development of elite patronage, protection and taxation of artisans, specialist traders and their activities is viewed as a strategy of mutual benefit and alliance between elites and specialists. By the later tenth and eleventh centuries some merchant-artisans, usually citizens of major towns, became indistinguishable from the lower aristocracy as they possessed both urban residences and rural estates. Yet, the foundation of their wealth and their growing power was specialist production, trade, portable wealth and the collective solidarity of urban societies.